2015
DOI: 10.1007/s11357-015-9778-9
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral leukocyte populations and oxidative stress biomarkers in aged dogs showing impaired cognitive abilities

Abstract: In the present study, the peripheral blood leukocyte phenotypes, lymphocyte subset populations, and oxidative stress parameters were studied in cognitively characterized adult and aged dogs, in order to assess possible relationships between age, cognitive decline, and the immune status. Adult (N = 16, 2-7 years old) and aged (N = 29, older than 8 years) dogs underwent two testing procedures, for the assessment of spatial reversal learning and selective social attention abilities, which were shown to be sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…In healthy beagle dogs, the numbers of CD4+ CD45+ and CD8+ CD45RA+ lymphocytes significantly decrease with age [78]. Moreover, aged dogs display a greater neutrophil-to-lymphocyte ratio and lower CD21+ B cells [79].…”
Section: Inflammation Leukocyte Recruitment and Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy beagle dogs, the numbers of CD4+ CD45+ and CD8+ CD45RA+ lymphocytes significantly decrease with age [78]. Moreover, aged dogs display a greater neutrophil-to-lymphocyte ratio and lower CD21+ B cells [79].…”
Section: Inflammation Leukocyte Recruitment and Activationmentioning
confidence: 99%
“…Therefore, studies performed in groups of dogs belonging to the same breed, such as the experimental beagle, may show differences in OS biomarkers [93]. Conversely, studies performed in populations of heterogeneous pet dogs may fail to detect differences in OS biomarkers between adult and aged dogs [79,94]. Moreover, the lifestyle of the subjects, in particular the different nutritional habits, can have a substantial impact on the degree of OS [79].…”
Section: Inflammation Leukocyte Recruitment and Activationmentioning
confidence: 99%
“…In aged canines, immunotherapy designed to reduce amyloid β (Aβ) pathology also improved cognitive function in the assessed tasks [112]. Mongillo et al [113] reported a higher monocyte count and percentage in cognitively impaired aged dogs compared with aged dogs with no cognitive impairment. These studies indicate that pro-inflammatory markers are associated with a decline in cognitive function.…”
Section: Cognitive Functionmentioning
confidence: 99%
“…Query: Please check the presentation of journal title of Ref. "Mongillo et al, 2015". Answer: The journal title is correct (Age), although the journal has recently changed its name to GeroScience…”
Section: Queries and Answersmentioning
confidence: 99%
“…Maze paradigms represent a valid tool in canine models to study the functions involved in spatial navigation (Craig et al, 2012;Macpherson and Roberts, 2010;Mongillo et al, 2015Mongillo et al, , 2013Parson et al, 2016) and the plusmaze has been proved one of the most effective type to assess navigation strategies both in humans and laboratory animals (Harris et al, 2012;Packard, 2009). A previous study performed by our research group demonstrated the feasibility of a T-maze paradigm to study spatial learning, long term memory and reversal learning (i.e.…”
mentioning
confidence: 99%